The Conservation Physiology of Bryophytes - Marko S. Sabovljević; Marija V. Ćosić; Bojana Z. Jadranin; Jovana P. Pantović; Zlatko S. Giba; Milorad M. Vujičić; Aneta D. Sabovljević (Plants, 2022)
An introduction to the conservation physiology of bryophytes is given. The insights into the problems, solutions and examples of the physiological approach to conservation within bryophyte representatives are discussed. The significance of experimental treatments of bryophytes is highlighted. The documentation of bryophyte functional traits and eco-physiological mechanisms in the conservation background for protection purposes is highlighted by the selected examples. The introduction of bryophytes into a new scientific field is resumed and some insights from specific case studies are presented.